Respectus Philologicus, 2011 Nr. 20 (25) - Bankauskaitė, Gabija (Respectus Philologicus, 2011)
CONTENTSI. PROBLEMS AND SOLUTIONSLoreta Ulvydienė, Giedrė Drėgvaitė (Lithuania). Linguistic Experience as the Projection of Urban Cognition in Literature...11Saule Altybayeva (Kazakhstan). Neomythologism of the Modern Kazakh Prose: Polycultural Discourse and Art Prospect Search...27Michał Mazurkiewicz (Poland). The Nature of Ritual... 40II. FACTS AND REFLECTIONSLaima Kalėdienė (Lithuania). Attitude Towards the Official Language According to the Data of Sociolinguistic Survey... 52Vadim V. Dementyev (Russia). Glamour as “The Old New Svetskost”?....65Elena Bonta, Raluca Galiţa (Rumunia). Joking as a Semiotic Practice and Means of Spiritual Survival. A Pragma-linguistic and Stylistic Approach... 80Irina Melnikova (Lithuania). The Gorris Defence, Or Nabokov on Screen... 95Jadvyga Krūminienė, Artūras Cechanovičius (Lithuania). On some Jungian Archetypes Reflected in Joseph Conrad’s Heart of Darkness... 107Ewa Anna Piasta (Poland). Axiological Horizons of the Short Story „The Dream of the Saint“ by Reinhold Schneider... 122Oleg N. Grinbaum (Russia). The Fourth Chapter of the Novel “Eugene Onegin” by A. S. Pushkin: Onegin’s Monologue in the Light of Rhythm and Meaning ... 133Valentina Litvinova (Russia). The Epistolary Heritage of A. Chekhov from Siberia (the Letters of the Writer from the Point of View of Time and Space)... 153Roma Konsevičiūtė (Lithuania). The “Giesmių Giesmė” (The “Song of Songs”) Motive Transformation in Antanas Jasmantas’ Lyrics... 162Eleonora Lassan (Lithuania). Conjunction зато as a Means of Realization of Psychological Compensation in the Russian Language.... 170Joanna Senderska (Poland). The Social Vocabulary Enrichment Based on Selected Cases of Polish Sociolects...181Danguolė Melnikienė (Lithuania). Peculiarities of the Specific Realia Expression in Lithuanian Bilingual Dictionaries... 192Marlena Chudzik (Poland). Toponomastic Scholars’ Problems... 202Daiva Aliūkaitė (Lithuania). Expression Ideals of Young Samogitians: Conscious Attitude...209Yuri Tambovtsev, Ludmila Tambovtseva, Juliana Tambovtseva (Rusija / Rosja). Functioning of the Continuous Tenses in Female and Male Variants of the American and British English Language...221Natalia Krasilnikova (Russia). Public Opinion in the Light of Cognitive Discourse Paradigm... 233III. OPINIONJelena Konickaja, Artur Zapolskij (Lithuania). Metaphors in Lithuanian and Slovenian Political Discourse... 243IV. SCIENTIFIC LIFE CHRONICLEConferencesViktorija Makarova (Lithuania). “Language and Method”. Krakow, 5–6 May, 2011...254Daiva Aliūkaitė (Lithuania). Project “Research on Modern Geolinguistics in Lithuania: Point Network Optimization and Dissemination of Interactive Dialect Information“...257Books reviewsDanutė Balšaitytė (Lithuania). Diagnosed. What next? ЛАССАН, Э., 2011. Лингвистика ставит диагноз... Очерк «духа эпохи» в свете данных лингвистического анализа... 260Dagnė Beržaitė (Lithuania). Remarks of Ungrateful Reader. DOSTOJEVSKIS, F., 2010. Apysakos I: Antrininkas, Žiemos pastabos apie vasaros įspūdžius, Užrašai iš pogrindžio... 267Announce... 271V. REQUIREMENTS FOR PUBLICATION...272VI. OUR AUTHORS...280
Keywords: none